(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes the role and importance of the prosecutor in the administrative courts of the Republic of Uzbekistan. Also, the participation of the prosecutor in administrative court proceedings in order to protect the interests of other persons, society and the state, in order to file an application to the court, give an opinion in the administrative court case, and file a protest against the administrative court documents is substantiated.